An enhanced formal inspection process to improve the efficiency and effectiveness of software inspection process / Navid Hashemi Taba - Navid Hashemi, Taba (2016)

(untitled)
In software development, it is important to detect and remove software defects as early as possible using a software inspection method. A formal inspection process (Process 1), was first introduced by Michael Fagan in 1976, and it was claimed that it can reduce about 38% of the defects in the software during development. Although some enhancements and improvements have been made to Process 1, and a few new inspection processes have been introduced, there are still weaknesses which include the absence of proper selection criteria for choosing the most suitable/qualified inspectors to conduct inspection on specific types of artefacts, some existing inspection processes do not have a database to help in the preparation of inspection checklists, and/or a database to store information on potential causes of each defect, which can provide a fast and easy reference to help in removing the defects. There is also a lack of inspection support tools that can help the software inspectors to conduct online inspection process which can save both time and costs for the inspection team members. This research is aimed at introducing an enhanced inspection process, ISIP (Process 2), by making some enhancements to overcome or reduce the weaknesses in Process 1. The enhancements include providing a method of selecting suitable inspectors based on their expertise and work experience; providing a defects database to store information on potential defects that are most commonly found in the requirements analysis and design phases, and which can be used as a reference for the preparation of inspection checklists; providing a database to store the possible causes of each of the defects stored in the defects database; and incorporating a few enhancements in the inspection process. To facilitate the selection of suitable inspectors and the inspection process, an inspection tool, ArSeC was developed using agile development techniques and MS SQL development environment. To determine whether the use of Process 2 with ArSeC can improve the inspection process, the process was evaluated using Paired T-test which compares the differences between Process 1 and v Process 2, in terms of the number of defects detected, inspection time, and the productivity of the inspectors. Two case studies were conducted in two companies and inspections were carried out on two software development projects to collect the data needed for the statistical test. The statistical test results show that at  = 0.05, the mean values of the number of defects detected, the inspection time, and the productivity of the inspectors when using Process 1 and Process 2 are 19.78 and 28.13; 220.97 minutes and 213.69 minutes; and 0.0891 and 0.1328, respectively. This shows that the use of ISIP effect significant improvement in the number of defects detected (i.e. difference = 8.35; 42.21%), and productivity of the inspectors (i.e. difference = 0.0437; 49.05%). However, there is only a slight improvement in the inspection time (i.e. difference = 7.28 minutes; 3.29%). It can be concluded that ISIP together with ArSeC improve the quality of inspection process in the two case studies.